Molecular and Functional Characterization of a Family of Amino Acid Transporters from Arabidopsis - Su, Yan-Hua (American Society of Plant Biologists, 2004)
More than 50 distinct amino acid transporter genes have been identified in the genome of Arabidopsis, indicating that transport of amino acids across membranes is a highly complex feature in plants. Based on sequence similarity, these transporters can be divided into two major superfamilies: the amino acid transporter family and the amino acid polyamine choline transporter family. Currently, mainly transporters of the amino acid transporter family have been characterized. Here, a molecular and functional characterization of amino acid polyamine choline transporters is presented, namely the cationic amino acid transporter (CAT) subfamily. CAT5 functions as a high-affinity, basic amino acid transporter at the plasma membrane. Uptake of toxic amino acid analogs implies that neutral or acidic amino acids are preferentially transported by CAT3, CAT6, and CAT8. The expression profiles suggest that CAT5 may function in reuptake of leaking amino acids at the leaf margin, while CAT8 is expressed in young and rapidly dividing tissues such as young leaves and root apical meristem. CAT2 is localized to the tonoplast in transformed Arabidopsis protoplasts and thus may encode the long-sought vacuolar amino acid transporter.